2007
DOI: 10.1177/000312240707200406
|View full text |Cite
|
Sign up to set email alerts
|

Who Survives on Death Row? An Individual and Contextual Analysis

Abstract: What are the relationships between death row offender attributes, social arrangements, and executions? Partly because public officials control executions, theorists view this sanction as intrinsically political. Although the literature has focused on offender attributes that lead to death sentences, the post-sentencing stage is at least as important. States differ sharply in their willingness to execute and less than 10 percent of those given a death sentence are executed. To correct the resulting problems wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 65 publications
0
34
0
Order By: Relevance
“…Recent research in Maryland (Paternoster and Brame 2008) (Pierce and Radelet 2005) provides equally persuasive evidence of racial disparities in the capital sentencing process in those states during the 1990s and 2000s. There also is evidence of racial disparity in federal capital sentencing (US Department of Justice 2000; that blacks, and to a lesser extent, Hispanics, who kill whites are executed a higher rates than other death-sentenced offenders ( Jacobs et al 2007); and that those who kill white females face higher odds of a death sentence than other offenders (Williams, Demuth, and Holcomb 2007).…”
Section: B Empirical Research On Race and The Death Penaltymentioning
confidence: 99%
“…Recent research in Maryland (Paternoster and Brame 2008) (Pierce and Radelet 2005) provides equally persuasive evidence of racial disparities in the capital sentencing process in those states during the 1990s and 2000s. There also is evidence of racial disparity in federal capital sentencing (US Department of Justice 2000; that blacks, and to a lesser extent, Hispanics, who kill whites are executed a higher rates than other death-sentenced offenders ( Jacobs et al 2007); and that those who kill white females face higher odds of a death sentence than other offenders (Williams, Demuth, and Holcomb 2007).…”
Section: B Empirical Research On Race and The Death Penaltymentioning
confidence: 99%
“…Echoing Jacobs, Qian, Carmichael and Kent (2007), this study also identified the importance of individual differences in terms of claiming innocence in the last statements. Parallel to Jones and Beck (2007), families were found to play a role in the last statements of death row inmates in that they referred to their own families and/or the victim's families while denying their crimes in their last statements.…”
Section: Conclusion and Suggestionsmentioning
confidence: 83%
“…Individual differences of death row inmates and contextual factors at state level deserve close attention since they could give us important clues about the delicacies of death and dying. Even minority presence and political ideology might come to the fore as part of above-mentioned factors in execution (Jacobs, Qian, Carmichael, & Kent, 2007).…”
Section: Review Of Literaturementioning
confidence: 99%
“…In terms of race and ethnicity in the United States, African American defendants are "5.3 percentage points more likely than whites to be sentenced to prison," and they "have twenty percent longer sentences than whites, on average, holding constant age, gender, and [the] recommended sentence length from [sentencing] guidelines" (Bushway and Piehl 2001, 752, 733). Research also has shown that prosecutors are more likely to seek the death penalty for black defendants than white defendants (Kleck 1981;Baldus, Woodworth, and Pulaski 1990;Jacobs et al 2007). Other studies have focused on the interaction between the races or ethnicities of the defendant and the victim (Baldus, Woodworth, and Pulaski 1990).…”
Section: Prior Research On Disparate Treatmentmentioning
confidence: 99%